ANALISIS PEMBELIAN PRODUK RAMAH LINGKUNGAN (GREEN PURCHASE) MELALUI KESADARAN TENTANG LINGKUNGAN, KESEHATAN DAN SIKAP PADA MAHASISWA STIE NGANJUK - Mahendra, Prasetya Tri; Bawono, Muhammad (Universitas Nusantara PGRI Kediri, 2022)
This study aims to analyze the purchase and use of environmentally friendly products (green purchase) among STIE Nganjuk students through socialization of awareness in being friendly to the environment, health, and attitudes. The researcher used the causal associative method using 100 students as respondents. For data collection using observation and questionnaire techniques, while to test the variables using multiple regression analysis through t test and F test (to test the hypothesis). The results of this research review using multiple linear analysis test which shows that of the variables of environmental awareness, health, and attitude, only the first variable positively and significantly affects the purchase intention of environmentally friendly products (green purchase) on STIE Nganjuk students.